2016
DOI: 10.1016/j.physletb.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anomalous HZγ couplings in γ-proton collisions at the LHC

Abstract: The HZγ coupling, which is highly sensitive to the new physics beyond the standard model, is studied through the process pp → pγp → pHX at the LHC. To this purpose, an effective Lagrangian, in a model independent approach, with dimension six operators is considered in this paper. New interaction terms regarding beyond the standard model physics include the Higgs boson anomalous vertices in both CP-even and CP-odd structures. A detailed numerical analysis is performed to scrutinize the accurate constraints on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 100 publications
(138 reference statements)
0
11
0
Order By: Relevance
“…It is impossible to cite all of the references here, but some representative ones might be Refs. [21,22, The semi-elastic single Higgs boson production can be studied through the process pp → pγp → pHqX at the LHC. This process consists of the subprocesses γq → Hq where q represents the quarks.…”
Section: Single Higgs Production Through Photon-proton Colli-sionmentioning
confidence: 99%
“…It is impossible to cite all of the references here, but some representative ones might be Refs. [21,22, The semi-elastic single Higgs boson production can be studied through the process pp → pγp → pHqX at the LHC. This process consists of the subprocesses γq → Hq where q represents the quarks.…”
Section: Single Higgs Production Through Photon-proton Colli-sionmentioning
confidence: 99%
“…The T-violating interactions of the top-quark have already been studied in the literature for a fixed CPviolating scale in the Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]; for example, CPviolation at future e + e − collider in t t production is investigated in Ref. [15], Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phenomenology studies based on the use of the proton tagging technique to study two-photon fusion interactions can be found in refs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Other interesting studies that aim also to describe photon fluxes in processes with proton dissociation, treated in the k T factorization framework, are presented in refs.…”
Section: Introductionmentioning
confidence: 99%